2021
DOI: 10.2196/26268
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Interventions in Prevention, Relapse, and Therapy of Mild and Moderate Depression: Scoping Review

Abstract: Background Depression is a major cause for disability worldwide, and digital health interventions are expected to be an augmentative and effective treatment. According to the fast-growing field of information and communication technologies and its dissemination, there is a need for mapping the technological landscape and its benefits for users. Objective The purpose of this scoping review was to give an overview of the digital health interventions used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 83 publications
(413 reference statements)
2
17
0
1
Order By: Relevance
“…In therapist-guided internet-delivered treatment, additional guidance and support are provided by therapists, coaches, or other professionals over the internet via chats, emails, and telephone [14][15][16]. In unguided treatment programs, the patients usually have access to the treatment content, and some programs provide automated prewritten feedback.…”
Section: Depressive Disorder and Treatment Over The Internetmentioning
confidence: 99%
See 1 more Smart Citation
“…In therapist-guided internet-delivered treatment, additional guidance and support are provided by therapists, coaches, or other professionals over the internet via chats, emails, and telephone [14][15][16]. In unguided treatment programs, the patients usually have access to the treatment content, and some programs provide automated prewritten feedback.…”
Section: Depressive Disorder and Treatment Over The Internetmentioning
confidence: 99%
“…In previously published reviews and meta-analyses on internet-delivered treatment for depression, randomized controlled trials (RCTs) have been the most prevalent methodological design [11,[14][15][16]. Etzelmueller et al [10] reviewed guided internet-delivered CBT focusing only on nonrandomized pre-post designs to evaluate the intervention effectiveness in a clinical setting and found evidence of both acceptability and effectiveness.…”
Section: Type Of Designmentioning
confidence: 99%
“…Clinicians have also indicated that it would be useful to include web-based interventions for adults seeking help for general mental well-being and suicidal ideation, which are issues commonly encountered in clinical practice but not covered by past reviews. We note that many reviews of the evidence for web-based interventions for specific disorders (eg, depression [29][30][31]) and for specific populations (eg, adolescents and young adults [32,33]) have been undertaken in recent years. Although these are helpful for researchers and intervention developers, they are less likely to meet the practical information needs of consumers and clinicians, as many of the interventions contained in the reviews are not available outside research settings, and others that are publicly accessible, have not been evaluated and therefore are not included in the reviews.…”
Section: Introductionmentioning
confidence: 99%
“…We identified the trials using the 2019 review by Tønning et al [ 14 ] on the methodological challenges of randomized controlled trials on smartphone-based treatment in psychiatry and the 2021 scoping review by Tokgöz et al [ 15 ] on digital health interventions for depression. We selected these papers as they offered a recent and comprehensive sample of studies from which we could explore coaching.…”
Section: Methodsmentioning
confidence: 99%